The impact of implementing universal design principles on user's satisfaction (Case study Erbil health care building Lobbies) - Ghafoor, Hazhin Nasih; Khayat, Mahmood Ahmed (Sulaimani Journal for Engineering Sciences, 2023)
All humankind should be taken into account, When designing any built environment, regardless of their physical ability or age. Everyone at some point in their lives faces different challenges, obstacles, and barriers. As a result, it's essential to maintain healthcare facilities that can accommodate people of diverse types and capacities. According to the aim of Universal Design principles, this ambition can become a reality. In Erbil, the current physical environment of healthcare facilities seems inadequate in mitigating the effects of the human life cycle and promoting unrestricted engagement for all individuals. This study examines the satisfaction level of hospital users (patient or Patient's family) within the lobby area and the application of universal design principles in healthcare buildings, focusing on the context of Erbil City. To achieve this, a face-to-face questionnaire survey was employed to measure user satisfaction, while a checklist was used to identify similarities and differences between the current design and universal design principles. Five hospital lobbies were studied from five different private hospitals in Erbil City. For analyzing user's satisfaction level descriptive statistics was used. The hospital lobbies under review show a strong degree of inclusivity and are generally well-received by their users, according to the aggregate mean score of (4.24) obtained from the answers of the survey. The relation between the universal design principles and the human satisfaction level inside the lobby was found to be positive. Despite the effect of the cultural background of the users to be satisfied with what is less than their actual needs. The findings of this study will provide insights into the extent to which the application of universal design principles in healthcare buildings affects user satisfaction. The results will help inform future design and planning strategies to create more inclusive and user-centered healthcare environments.
Keywords: Universal Design Principles; Healthcare Buildings; User Satisfaction; Erbil City